Takhrij and Syarah Hadith of Agrotechnology: The Importance of Using Land for Cultivating Plantations - Muhamad Rangga Yudistira; Wahyudin Darmalaksana; Cecep Hidayat (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to farming. This research method is a qualitative type through literature study and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is how important it is to cultivate crops as recommended by the Prophet Muhammad. The conclusion of this research is takhrij and syarah hadith about the importance of farming which provides many benefits for humans and other living things.